Perbandingan Sistem Hukum Civil Law dan Common Law - Feri Pramudya Suhartanto; Yenny Febrianty (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The civil law and common law systems are two primary approaches in global legal systems, each with unique principles, histories, and applications. Civil law, widely implemented in most European countries and those influenced by the Roman system, is based on the systematic codification of written laws. The main sources of this law are legal codes and legislation issued by legislative bodies. Judges interpret the law by referring to the established legal texts. On the other hand, common law developed in England and subsequently influenced countries that were once British colonies, such as the United States and Australia. This system emphasizes legal precedents set by judges' decisions in previous cases. Its principle is the doctrine of stare decisis, which means respecting previous decisions when similar cases arise in court. Key differences between them include the way laws are formed, the role of judges, and the approach to evidence. Civil law tends to be more structured and based on legislation, whereas common law is more flexible, relying on case interpretations to form the law. Nonetheless, globalization has led to the adoption of elements from both systems in other countries, creating hybrid or mixed systems in modern legal practice.